Correlation of chemical compositions of cassava varieties to their resistance to prosiephanus truncatus horn (coleoptera: bostrichidae) (2015)
The preference of cassava as a major host by Prostephonus truncotus Horn is a major constraint to ample production of cassava, Manihot esculenta Crantz and storage. This study analyzed the nutritional and secondary metabolite compositions in 15 cassava varieties, evaluated levels of damage and reproduction by P. truncatus, and assessed their resistance to attack. One hundred grams of dried cassava chips in 250-ml Kilner jars were infested with 10 adult larger grain borerof 0-10 days old and held for 3 months. The nutritional and secondary metabolites compositions of the dry cassava chips were determined using the method of Association of Analytical Chemists. Chip perforation rates in the cassava varieties ranged from 17.7 to 71.6%. The weight of cassava powder varied by about threefold. The final number of larger grain borer in the cassava varieties varied by about sixfold with 63 in 01/0040 and 379 in 01/1368. Hydrocyanic acid content varied by over 10-fold and correlated negatively with number of larger grain borer. Flavonoid content varied by ~10%. Tannins and saponin content of the cassava negatively correlated with number of adult P. truncatus. The cassava varieties 95/0166, 92/0326, 01/0040, 05/0024, and 34 91934 had selection index <0.8 and were classified as resistant to larger grain borer damage, while others with selection index >0.8 were classified as susceptible. The resistance to high damage in the resistant varieties was conferred by secondary metabolites such as tannins, saponins, alkaloids, and hydrocyanic acid content. The genetic variation in cassava varieties could be explored to breed resistant cassava varieties for use in larger grain borer-endemic areas.